Peserta Didik dalam Pandangan Imam Al-Ghazali - Lubis, Ihsan Rinaldi; Suryani, Ira; Innayah, Azzira; Azzahra, Nazwa; Hafiza, Nur (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Imam Al-Ghazali believed that students have their own potential to achieve moral and spiritual perfection. The role of educators is very important and influential in helping them achieve this goal, with a focus on spiritual and moral development. This journal outlines Al-Ghazali's views on the potential of students, spiritual and moral development, and educational strategies that can be taken from the perspective of Imam Al-Ghazali. This research was conducted using a qualitative method, with analysis and literature study. Students are humans who are experiencing growth and development, especially in physical and mental aspects. Imam Al-Ghazali's perspective on students and Islamic education is still relevant and applicable in the context of modern education, which can help educators develop holistic educational strategies focused on the spiritual and moral development of students.